The Effect Of Internal Communication And Ability On Self Development And Organizational Citizenship Behaviour Employees Of PT. Pulo Mas Jaya, Jakarta - Gizca Mahanti Aulia Almas; Hosni Suradji; Muhammad Anhar (BPJP - STEI, 2020)
Abstract—This study aims to examine the influence of internal communication and Ability on self-development and Organizational Citizenship Behavior at PT. Pulo Mas Jaya, Jakarta. This research is a quantitative research with a survey method analyzed using SEM (Structural Equation Modeling) with the Smart Partial Least Square (PLS) 3.0 software program. The population of this study is the company PT. Pulo Mas Jaya, Jakarta. The sample was determined based on the proportional random sampling method with a sample size of 86 employees. The data used are primary data, data collection using an instrument in the form of a questionnaire. Testing uses Outer Model analysis, Inner Model analysis, and hypothesis testing (t-statistical test). The results of this study prove that: (1) internal communication has a positive direct effect on self- development, (2) Ability has a positive direct effect on self- development, (3) internal communication has a positive direct effect on Organizational Citizenship Behavior, (4) Ability has a positive direct effect on personal development. Organizational Citizenship Behavior, and (5) self- development have a positive direct effect on Organizational